Wissenschaftsreflexion: What is it? What is the need for it? Contemporary challenges for studies in science - Eva Barlösius; Martin Carrier; Alexander Bogner; Michael Butter; Paula Diehl; Max-Emanuel Geis; Michael Jungert; Carsten Reinhardt; Torsten Wilholt; Michael Zürn (Minerva, 2025)
Academic freedom and societal respect for science have been decreasing in the past years in the wake of growing nationalism, authoritarianism, and fundamentalism. Even in liberal democracies, science has been attacked by anti-science movements. One of the reasons for the weakening credibility of scientific knowledge is its exaggerated use in framing policy questions. Conflicts about interests and values are transformed into controversies about the validity and relevance of studies and data. Since scientific knowledge is a foundation of liberal democratic knowledge societies, a refusal to recognize it as a legitimate basis of decision-making undermines democratic deliberation and societal participation. We propose Wissenschaftsreflexion as a specific approach to addressing the challenges posed by the influence of science on political and social affairs and the unfavorable response to this influence by parts of developed knowledge societies. Wissenschaftsreflexion is integrative in collaborating with the various home disciplines of the humanities and the social sciences, and explicitly normative in judging the conditions and limitations of scientific advice and in taking liberal democracies as the basis of rational, fact-based policy decisions. The academic system alone cannot defend the appropriate use of scientific knowledge against unfounded threats. Attacks should be recognized as a general societal and political challenge and not be treated as merely a concern of scientists and the science system. Scientific knowledge, scholarship, and the science system need to be protected against unfounded assaults to be able to fulfill the societal tasks assigned to them in liberal democratic knowledge societies.
Keywords: 300; Knowledge society; Attack; Research approach; Epistemic judgment; Liberal democracies